2019
DOI: 10.1186/s13063-019-3781-x
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of reporting in abstracts of randomized controlled trials in subscription and open access journals: cross-sectional study

Abstract: BackgroundOpen access (OA) journals are becoming a publication standard for health research, but it is not clear how they differ from traditional subscription journals in the quality of research reporting. We assessed the completeness of results reporting in abstracts of randomized controlled trials (RCTs) published in these journals.MethodsWe used the Consolidated Standards of Reporting Trials Checklist for Abstracts (CONSORT-A) to assess the completeness of reporting in abstracts of parallel-design RCTs publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…It is recommended that 250 to 300 words be sufficient to address all of the items in the CONSORT-A checklist [ 7 ]. Our study also showed that better reporting scores were associated with more words (> 250) in abstracts, which was indicated in other studies [ 20 , 36 , 37 ], although nearly half journals included in our study limit words in the abstract to less than 250, which may be due to journal preference or traditional format. The fewer word limitation for abstracts may lead to the absence of some important information.…”
Section: Discussionsupporting
confidence: 83%
“…It is recommended that 250 to 300 words be sufficient to address all of the items in the CONSORT-A checklist [ 7 ]. Our study also showed that better reporting scores were associated with more words (> 250) in abstracts, which was indicated in other studies [ 20 , 36 , 37 ], although nearly half journals included in our study limit words in the abstract to less than 250, which may be due to journal preference or traditional format. The fewer word limitation for abstracts may lead to the absence of some important information.…”
Section: Discussionsupporting
confidence: 83%
“… Essential item of abstract: we identified essential information/items of the abstract as obligate reporting information the absence of which would compromise the reporting quality of the abstract, irrespective of the information being reported in the full-text article or not. Examples are; reporting at least one study objective, reporting study population characteristics, type of intervention/treatment, and so forth [ 1 , 6 , 7 , 19 , 20 ]. Non-essential item of abstract: we identified non-essential information/items of the abstract as an occasionally obligate reporting information depending on the study context and settings, and the absence of which would not necessary compromise the reporting quality of the abstract.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting quality of abstract refers to the fulfilment of a certain reporting item scenario of the abstract per se and irrespective of the information present in its corresponding full-text article [ 1 , 6 , 7 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations